The Intolerance of Uncertainty and “Untact” Buying Behavior: The Mediating Role of the Perceived Risk of COVID-19 Variants and Protection Motivation - Zhao, Shunying; Ye, Baojuan; Wang, Weisha; Zeng, Yadi (Frontiers in Psychology, 2022)
Draw on the protection motivation theory, this study investigated the impacts of intolerance of uncertainty on ‘untact’ buying behavior, and examined the sequential mediating role of the perceived risk of COVID-19 variants and protection motivation. A total of 1564 (Mage = 20.75, SD = 1.92) young individuals participated in the survey. The serial mediation analysis results reveal that intolerance of uncertainty influences one’s ‘untact’ buying behavior through “perceived risk of COVID-19 variants - protection motivation”. Both internal (intolerance of uncertainty, protection motivation) and external (risk of COVID-19) factors worked together to accelerate the transition of individuals’ consumption behavior during COVID-19 pandemic. Therefore, our findings generate important implications for public mental health and economic recovery in the post-COVID-19 era.